Robot‐assisted single‐port radical prostatectomy: A phase 1 clinical study - Chi‐Fai Ng; Jeremy Yuen‐Chun Teoh; Peter Ka‐Fung Chiu; Chi‐Hang Yee; Chi‐Kwok Chan; Simon S.M. Hou; Jihad Kaouk; Eddie Chan (2019)
Objective To investigate the safety and feasibility of robot‐assisted single‐port radical prostatectomy using the da Vinci single‐port surgical system. Methods This was a prospective phase 1 clinical study of prostate cancer patients undergoing robot‐assisted single‐port radical prostatectomy using the da Vinci single‐port surgical system. Primary outcome measures included the conversion rate and 30‐day complications after surgery. Secondary outcome measures included operative time, blood loss, hospital stay, duration of catheterization, final pathological outcomes and number of lymph nodes yielded at pelvic lymphadenectomy. Results From February to August 2017, 20 patients were included in the present study. The mean age was 67.7 ± 6.0 years. The mean preoperative prostate‐specific antigen level was 15.3 ± 11.3 ng/mL, and the mean prostate size was 36.6 ± 15.5 mL. Preoperatively, 12 (60%) patients had a Gleason score of 6, four (20%) had a Gleason score of 7 and four (20%) had a Gleason score of 8–10. The mean operative time was 208.9 ± 35.2 min, and the mean blood loss was 296.3 ± 220.7 mL. None of the patients required conversion. The mean hospital stay was 5.0 ± 1.7 days. Among the patients, six (15%) had T2a disease, one (5%) had T2b disease, seven (35%) had T2c disease and nine (45%) had T3a disease on final pathology. A mean number of 8.3 ± 7.1 lymph nodes were yielded at pelvic lymphadenectomy. There were no intraoperative complications. The observed postoperative complications were Clavien grade I–II, and all resolved with conservative management. Conclusion Robot‐assisted single‐port radical prostatectomy using the da Vinci surgical system is safe and technically feasible.